The sisters of Summit Avenue - Cullen, Lynn (Gallery Books, 2019)
From the bestselling author of Mrs. Poe and Twain's End comes a novel set during the Great Depression following two estranged sisters and their mother--who has spent a lifetime hiding a desperate secret that could dismantle the entire family.